Growth Curve, Morphological and Molecular Characterization of Two Strains of Trypanosoma cruzi (Kinetoplastida, Trypanosomatidae) isolated from Triatoma sherlocki (Hemiptera, Reduviidae, Triatominae) - Kunii, Gabriela Kinue Watase [UNESP]; Falcone, Rossana [UNESP]; Clementino, Leandro da Costa [UNESP]; Rosa, João Aristeu da[UNESP]; Nascimento, Juliana Damieli; Belintani, Tiago; Oliveira, Jader de; Ribeiro, Aline Rimoldi (FapUNIFESP (SciELO), 2022)
Background: Trypanosoma cruzi presents great variability in morphology, virulence, pathogenicity, avoidance of the host immune system, and antigenic constitution, associated with different clinical manifestations of the disease. Methods: Two strains of T. cruzi were cultivated in liver infusion tryptose to determine growth kinetics, morphometry and molecular characterization using restriction fragment length polymorphism polymerase chain reaction. Results: The biological parameters showed sharp growth by the 7th day. Morphologically, both strains showed short and thin forms and were classified as Group I. Conclusion: Group TcI presents cardiac manifestations and T. sherlocki is adapting to the home environment, requiring attention to future problems.
Keywords: Chagas disease; Epidemiology; Trypanosoma cruzi; Vector biology